Regional pattern of physical inactivity in Croatia - Milošević, Milan, liječnik (Array, 2009)
Summary: The aim of this paper was to analyze the regional pattern of physical inactivity in Croatia based on the Croatian Adult Health Survey 2003 data. A total of 9,070 adult respondents were included in this study. In men, the highest prevalence of physical inactivity was recorded in the City of Zagreb (39.6%), and it was significantly higher than in Central (25.6%), Coastal (25.6%) and Mountainous region (14.1%). Mountainous region had significantly lower prevalence of physical inactivity compared to any other region, except the Central region. The highest prevalence of physical inactivity in women was also recorded in the City of Zagreb (43.6%), and it was also significantly higher than in all other regions. The lowest prevalence of physical inactivity was recorded in Eastern Region (24.7%) The highest levels of physical inactivity in both in both genders were recorded in urban regions, suggesting that intervention measures in terms of health promotion should be undertaken, with strong emphasis on the people living in urban settings